Challenges in Implementing the Merdeka Curriculum in Early Childhood Education: A Case Study in Kindergarten - Cahya, Intan; Kamariah Hasis, Pertiwi; Mahmudah BuluÔÇÖ, Rifa'ah (Journal of Islamic Education Students (JIES), 2025)
The Merdeka Curriculum in Indonesia offers flexibility in the implementation of learning; however, its application at the Early Childhood Education (PAUD) level faces various challenges. This study aims to describe the implementation of the Merdeka Curriculum at TK Andi Bintang, Palopo City, highlighting the challenges encountered during its execution. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation. The collected data were analyzed using thematic analysis techniques. The findings indicate that despite the curriculum's implementation, significant challenges persist, including limited resources, inadequate facilities, insufficient teacher understanding of the curriculum, and low parental involvement in the learning process. These challenges impact the effectiveness of the curriculum implementation, although the potential for children's development remains evident if these issues are addressed. The study emphasizes the need for further efforts to enhance teachers' understanding, improve facilities, and strengthen parental support in children's learning.┬á┬á